Atmospheric Observations over Central Japan Using a Helicopter: Measurements of Hydrogen Peroxide and Formaldehyde - Koichi Watanabe; Mei Jia Jin; Xiao Jing Song; Liu Yang; Kaede Genmoto; Yumeko Ichikawa; Yu Nagahori; Kanji Chimura; Haruka Nagamura (Aerosol and Air Quality Research)
Abstract Hydroperoxide, formaldehyde (HCHO), ozone (O3), sulfur dioxide (SO2) concentrations, and number concentrations of aerosol particles were measured made over the coastal site of the Sea of Japan in central Japan during the cold and autumn seasons using a helicopter. During the cold months, the hydrogen peroxide (H2O2) concentrations were usually below 1 ppb, lower than the SO2 concentrations—a condition known as “Oxidant Limitation”. The concentrations of H2O2 were also lower than the concentrations of HCHO, suggesting that the formation of hydroxymethanesulfonate might have been more likely than that of sulfate in the liquid phase. The H2O2 concentrations were generally higher in autumn than in the cold season, and they were higher than the SO2 concentrations in the high-altitude atmosphere. However, few measurements were taken in autumn, and future observations are required.